Tissue and serum EGFR as prognostic factors in malignant pleural mesothelioma - Gaafar, Rabab; Bahnassy, Abeer; Abdelsalam, Ibrahim; Kamel, Mahmoud M.; Helal, Amani; Abdel-Hamid, Amany; Eldin, Nelly Aly; Mokhtar, Nadia (Lung cancer (Amsterdam, Netherlands), 2010)
Malignant pleural mesothelioma (MPM) is an asbestos related aggressive tumor. Asbestos causes genetic modifications and cell signaling events that favor resistance to chemotherapy. A variety of receptor tyrosine kinases have been identified to play a central role in various aspects of tumorigenesis. Epidermal growth factor receptor ( EGFR) is overexpressed in a variety of epithelial malignancies including lung cancer in which EGFR aberrations not only predict response to EGFR tyrosine kinase inhibitors but also indicate tumor progression. However in MPM, the role of EGFR is less clear. This study was designed to identify serum and tissue EGFR levels in patients with MPM and to evaluate the relationship between serum and tissue EGFR levels and clinicao-pathological prognostic factors and survival. We investigated 71 cases of MPM for EGFR expression in tissue. Serum EGFR was assessed in 40 out of those 71 cases and 20 healthy subjects as a control. Pre-treatment serum EGFR levels were measured using quantitative enzyme-linked immunosorbent assay. Tissue EGFR protein overexpression was assessed by immunohistochemistry and gene amplification was assessed by the chromogen in situ hybridization (CISH) technique. Results were correlated with the clinical–pathological factors of the patients and overall survival (OS). Out of the 71 patients included in the study, 19 had undergone extrapleural pneumonectomy. As for the rest of the patients, 46 received chemotherapy while 6 had only best supportive care. EGFR immuno-reactivity was detected in 74.6% of the cases, 37 (52.1%) cases were positive for EGFR gene amplification by CISH, 31 of them revealed moderate to high (++, +++) EGFR immuno-reactivity. Elevated serum EGFR >2.5 ng/ml (the median concentration of EGFR in MPM) was reported in 45% of the cases. The overall response rate (RR) for the 46 treated patients who received chemotherapy was 24.1%. After a median follow up of 29 months, the median overall survival (OS) was 10 months. Elevated serum and tissue EGFR is significantly associated with advanced disease stage. However neither EGFR overexpression in tissues nor high serum levels were associated with survival rates. EGFR expression is a common feature in MPM patients. High pre-treatment levels of serum EGFR are associated with advanced stage but not with reduced OS. Detailed mutational analysis of EGFR on a larger number of patients is still needed to clarify the exact role of EGFR in MPM patients.